Novel final focus design for future linear colliders. - Raimondi, P; Seryi, A (2001)
The length, complexity, and cost of the present final focus designs for linear colliders grow very quickly with the beam energy. In this Letter, a novel final focus system is presented and compared with the one proposed for the Next Linear Collider (NLC Zeroth-Order Design Report, edited by T. O. Raubenheimer, SLAC Report No. 474, 1996). This new design has fewer optical elements and is much shorter, nonetheless achieving better chromatic properties. Moreover, the new system is more suitable for operation over a larger energy range.